Network Society and Social Movement: Message Reception among Instagram Users - Monika Sri Yuliarti; Muhnizar Siagian; Andri Kusuma Wardaningtyas (Ikatan Sarjana Komunikasi Indonesia, 2020)
In the dynamics of a state, any change can happen through a social movement as an initial stage. Studies about it have been conducted since the 1940s. Nowadays, as the shift of the era involves communication technology, the model of the social movement has changed as well. Collectivity dominated the social movement in the past, but connectivity is more prominent nowadays as the network society era emerges. The purpose of this research is to explore the social movement in the network society era through an Instagram account, @ketimbang.ngemis.yogyakarta along with the message reception among the Instagram users. Using Stuart Hall’s theory of message reception, this study employed snowball as the technique sampling. After analyzing five posts on @ketimbang.ngemis.yogyakarta Instagram account and having an interview with eight informants, there were two conclusions. It is found that there is a shift in the model of social movement. In the past, social movements were dominated by demonstrations, in which a group of people gathered in a particular place, and relied on oratory skills. Meanwhile, at present, many social movements have made use of social media, one of which is Instagram. The photos in Instagram are used to show marginalized groups which can attract sympathy, empathy, and attention of social media users as an initial stage to the social movement. Moreover, the social media users tend to be a negotiated code type in the reception of social movement message.